E-LEARNING RESOURCES IN HIGHER EDUCATION: OBSTACLES AND OPPORTUNITIES - Bolshakova, Natalia; Mitchenko, Zinaida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of the work is to create and use an electronic training course for University students (bachelor's level) on the topic "Fundamentals of Linguistics" on the Moodle platform. The methodological basis of the work is the principle of consistency, which correlates with the subject area of the project. In connection with the ideas of instructional design the modeling and design methods are also leading. With the help of private methods, methodological recommendations, skills of practical analysis of language phenomena are worked out. The novelty of the project consists in the integrated development of an e-learning course that has no analogues and uses the approved platform productively, based on the author's content. The analysis of distance learning in higher education in relation to the theoretical humanitarian discipline showed the great possibilities of the Moodle system: multi-channel information delivery, variability of forms, flexibility of the structure, taking into account all types of educational activity of students. Despite the relevance and demand for distance education, the work revealed its shortcomings: the lack of direct communication between the student and the teacher, and other psychological and pedagogical factors that form the academic environment. It is recommended to use the e-learning course developed and structured taking into account new trends in instructional design as a tool for supporting mixed education.